Retention of physiological adaptations to heat in highly trained rowers - Gunning, L. N.; Anson, J. M.; Hahn, A. G. (Medicine & Science in Sports & Exercise, 1997)
Adaptation to heat results in physiological changes such as reductions in heart rate and rectal temperature, plasma volume expansion, and increased sweat loss. In untrained Ss these changes are retained for a period of time following heat exposure. If the same changes occurred in highly-trained athletes, they could provide an advantage during competitions in the heat. Highly trained rowers (M = 12; F = 12) were matched and allocated to two groups (N =12) and were exposed to the same training program for 26 days in hot (32 degrees Celsius; 34% relative humidity) or moderate (14 degrees Celsius; 72% relative humidity) environments. Sub-maximal ergometer tests were conducted twice weekly as well as pre- and post-training evaluations. The hot-environment group showed significant reductions in heart rate and rectal temperature and increases in plasma volume and sweat loss. After 2-4 days of reintroduction to moderate temperatures only sweat loss remained changed in the "hot" group. Heat adaptations were lost quickly. Implication. Adaptations that occur while training in the heat are lost quickly (2-4 days) in highly trained athletes. When performing in the heat, there should be no break that might induce loss of adaptive responses between heat adaptation training and a competition.